2015
DOI: 10.1016/j.ejpb.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Formulation to target delivery to the ciliary body and choroid via the suprachoroidal space of the eye using microneedles

Abstract: In this work, we tested the hypothesis that particles injected into the suprachoroidal space can be localized at the site of injection or broadly distributed throughout the suprachoroidal space by controlling polymeric formulation properties. Single hollow microneedles were inserted into the sclera of New Zealand White rabbits and injected non-biodegradable fluorescently tagged nanoparticles and microparticles suspended in polymeric formulations into the suprachorodial space of the eye. When formulated in sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…One studies mentions injected fluid not crossing the midline but does not offer an explanation as to why this is (Gu et al, 2015). Other studies have shown that formulations designed to keep SCS open after injection allow particles to redistribute within SCS and cover both hemispheres of the eye (Kim et al, 2015), although re-analysis of particle spread indicates lower particle concentration overlaying LPCAs compared with elsewhere (data not shown).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…One studies mentions injected fluid not crossing the midline but does not offer an explanation as to why this is (Gu et al, 2015). Other studies have shown that formulations designed to keep SCS open after injection allow particles to redistribute within SCS and cover both hemispheres of the eye (Kim et al, 2015), although re-analysis of particle spread indicates lower particle concentration overlaying LPCAs compared with elsewhere (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies using particles suspended in HBSS have indicated that particle spread occurs at the time of injection, after which the particles do not move (Kim et al, 2014b, c; Kim et al, 2015; Patel et al, 2012; Patel et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…2). We and others have seen that injection of larger volumes leads to spread over a larger area of the suprachoroidal space [41, 4749]. To localize our formulation at the site of injection at the supraciliary space, we wanted to minimize the injection volume and therefore needed to give multiple injections in order to deliver the target dose.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used the two-dimensional (2D) circumferential spread of particles injected into the SCS as the primary metric of distribution (Kim et al, 2014a, b; Kim et al, 2015; Patel et al, 2012; Patel et al, 2011). Though many studies have investigated the distribution of particles (Chen et al, 2015; Kim et al, 2014a; Kim et al, 2015; Patel et al, 2012; Patel et al, 2011) and molecules (Kim et al, 2014b; Olsen et al, 2011; Patel et al, 2012; Tyagi et al, 2013; Wang et al, 2012) independently, to our knowledge, no study has examined the distribution of particles and molecules injected into the SCS simultaneously, or imaged the distribution of polymeric formulation excipients in the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…Though many studies have investigated the distribution of particles (Chen et al, 2015; Kim et al, 2014a; Kim et al, 2015; Patel et al, 2012; Patel et al, 2011) and molecules (Kim et al, 2014b; Olsen et al, 2011; Patel et al, 2012; Tyagi et al, 2013; Wang et al, 2012) independently, to our knowledge, no study has examined the distribution of particles and molecules injected into the SCS simultaneously, or imaged the distribution of polymeric formulation excipients in the SCS. Better understanding of how particles move relative to the formulation will enable the rational design of formulations that control particle spreading in the SCS.…”
Section: Introductionmentioning
confidence: 99%